Principles of Differentiation of Teaching - Šiaučiukėnienė, Liuda (Acta Paedagogica Vilnensia, 1996)
The aims of the educational reform in Lithuania can be implemented if principles of differentiation of teaching will be realized in schools. In order to accomplish this task the worldwide tendencies in this field should be explored and analysed. The article presents the historical aspect of differentiation of teaching, starting with the ideas of J. J. Rousseau and proceeding to the concepts of G. S. Hall, J. Dewey, M. Montessori and other authors. The contemporary outlook is represented by A. Maslow and theory of humanistic education. The article also reviews the specificity of differentiated learning during the periods of childhood, adolescence and youth. The basic trends in Soviet pedagogy concerning differentiation of teaching are presented as well. The article concludes that differentiated learning creates a new type of relationship between the individual and the school. It enables pupils to choose the most suitable forms of working at school.